Preliminary studies on propagating natural mason bee (mixed Osmia cornuta and O. rufa) populations in artificial nesting media at the site for fruit orchard pollination - Benedek, P. (International Journal of Horticultural Science, 2008)
Preliminary field management studies were made to increase the population density of native early spring Osmia species (O. cornuta, O. rufa) at fruit tree plantations in Hungary. Initial bee activity around artificial nesting media and the population increase during consecutive years were much smaller at large commercial fruit orchards under intense chemical plant protection than in small mixed fruit plantation with moderate or low pesticide usage. Osmias accepted all the four kinds of tested artificial nesting media (reed, bamboo rods, hardwood blocks and light walling blocks with drilled holes). Reed provided the best nesting conditions so it is suggested to be used in the practice. Calculations showed that under favourable conditions more than 50 to 100 thousand incoming flights (arrivals or landings) occurred in a single day around a single bee shelter and this makes enormous number of possible bee visits at fruit tree flowers. For this reason it is strongly recommended to put simple bee shelters filled with artificial nesting media into fruit orchards. Experiences show that the population sizes of Osmias increase during consecutive years without any specific additional maintenance except providing shelters and nesting media.